Pengujian Usability Pada Aplikasi Auto Reply For Messenger Menggunakan SUS - Nasrulloh Isnain; Han Sulaiman; Rahmatika Rahmatika (Explorer, 2021)
Marketplace is an important intermediary between sellers and buyers in cyberspace. Marketplace sites are third parties in online transactions. Many resellers use the site to make sales transactions. However, when we engage in online sales, there are many factors that must be considered, one of which is replying to customer chat messages. This is very important in the world of sales even required to respond quickly. The problem is that sometimes resellers have activities other than selling online, so sometimes customer messages are late in responding and even unresponsive. This study aims to determine how effective and efficient it is in handling customers using Chat Bot Messenger. The research method used is blackbox to determine the application function is running well and to evaluate the usability of the system using the System Usability Scale (SUS). The test results produce an average value of 81 which means users like the application that is used because it is able to provide convenience during sales transactions.